Amplified spontaneous emissions from (oxalato)(dibenzoylmethanato)boron - LIM, H; YAP, S; TOU, T; NG, S (2005)
Amplified spontaneous emissions (ASE) from two boron-containing organic compounds, (oxalato)(dibenzoylmethanato)boron, were obtained for the first time using a nitrogen laser as the pump source. Compared to commercially available laser dyes, there were only small red shift and minimum broadening in the peak ASE wavelength. ASE conversion efficiencies obtained were 8-10% in chloroform solution and 5% when doped in thin films of poly(methyl methacrylate). (c) 2004 Elsevier B.V. All rights reserved.